2013
DOI: 10.1371/journal.pone.0064413
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Mitochondrial DNA as Biomarker Linking Environmental Chemical Exposure to Early Preclinical Lesions Elevation of mtDNA in Human Serum after Exposure to Carcinogenic Halo-Alkane-Based Pesticides

Abstract: There is a need for a panel of suitable biomarkers for detection of environmental chemical exposure leading to the initiation or progression of degenerative diseases or potentially, to cancer. As the peripheral blood may contain increased levels of circulating cell-free DNA in diseased individuals, we aimed to evaluate this DNA as effect biomarker recognizing vulnerability after exposure to environmental chemicals. We recruited 164 individuals presumably exposed to halo-alkane-based pesticides. Exposure evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 43 publications
0
43
0
3
Order By: Relevance
“…Plasma mtDNA levels are also significantly increased in patients with tissue injury and various tumors [15,20,21]. The mechanism that cells use to release free circulating DNA into the blood is still not elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma mtDNA levels are also significantly increased in patients with tissue injury and various tumors [15,20,21]. The mechanism that cells use to release free circulating DNA into the blood is still not elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…The steady mitochondrial DNA level in plasma, also shown by others (Beiter et al 2011), most likely excludes apoptosis as main mechanism of DNA release following exhaustive exercise. The different nature and release mechanisms of cell free mtDNA and nuclear DNA could be also reflected by their lack of correlation in some diseases (Budnik et al 2013). It was suggested that cfDNA concentrations increase by unknown active or passive mechanisms in response to acute stress during exercise (Breitbach et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of mtDNA levels was performed by quantitative real-time PCR (QPCR) essentially as described by Budnik et al [11]. Briefly two primer sets specific for the mitochondrial ribosomal 16S RNA were used: One pair amplified a 74-bp fragment that represented total mtDNA and included DNA released by apoptotic cells (mtDNA-74).…”
Section: Mitochondrial Dna Quantification (Mtdna)mentioning
confidence: 99%